2009
DOI: 10.2174/157018009787847864
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Oligomerization of Aerolysin from Aeromonas Hydrophila: Homology Modeling and Docking Approach for Exploration of Hemorrhagic Septicemia

Abstract: Aerolysin (Aer) is a pore forming toxin that plays important role in pathogenesis of Aeromonas hydrophila which causes hemorrhagic septicemia in aquatic and terrestrial animals including humans. Aerolysin aggregates in the forms of oligomers on the surface of animal RBCs and its ability to bind with Glycosylphosphatidyl inositol (GPI) anchored protein receptor. The primers were designed for Aer gene and amplified to target the complete ORF of Aeromonas hydrophila; later it was sequenced. Homology modeling was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 27 publications
1
33
0
Order By: Relevance
“…All the above properties of peptide deformylase satisfied the need for good quality of the 3-D model. The previous study also supported our data regarding the quality of the 3-D model and the amino acids present in allowed region of the Ramachandran plot [10,31,38].…”
Section: The 3-d Modeling Of Peptide Deformylasesupporting
confidence: 88%
See 4 more Smart Citations
“…All the above properties of peptide deformylase satisfied the need for good quality of the 3-D model. The previous study also supported our data regarding the quality of the 3-D model and the amino acids present in allowed region of the Ramachandran plot [10,31,38].…”
Section: The 3-d Modeling Of Peptide Deformylasesupporting
confidence: 88%
“…The effectiveness of actinonin against PDF of E. coli and Staphylococcus aureus has been further tested and it has been found that similar concentrations could control the growth of both bacteria [35]. Molecular docking has been used for the screening of potent drug molecules by targeting the aerolysin of A. hydrophila [38] and 3-oxoacyl-acyl carrier protein synthase II of Mycobacterium tuberculosis [56]. Sharma et al [57] have tested BB-3497 and actinonin and both were found to be potent drugs against the PDF of M. tuberculosis at low concentrations.…”
Section: Screening Of Potent Drugs and Phylogenetic Analysismentioning
confidence: 99%
See 3 more Smart Citations